The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acscentsci.9b00379
|View full text |Cite
|
Sign up to set email alerts
|

An Asymmetric Electrochemical System with Complementary Tunability in Hydrophobicity for Selective Separations of Organics

Abstract: Conducting polymers modified with redox-active moieties or amphiphilic surfactants are promising adsorbent materials for the separation of neutral organic species from water. We develop an asymmetric system combining a polyvinylferrocene–polypyrrole hybrid (PVF–PPy) and an amphiphilic surfactant dioctyl sulfosuccinate (AOT)-doped polypyrrole (PPy(AOT)) that have complementary hydrophobicity tunability in response to electrochemical modulations. Both materials are hydrophobic in their respective neutral states,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Clearly, the data indicate that the incorporation of ZnO NPs seems to be able to slightly improve the sensitivity. However, the modified electrodes based on only any single material, even the simple combination of two components including MWCNTs, PMAEFc, and ZnO NPs surprisingly do not show well-defined redox peak currents, which is different from the results reported by quite a lot of references in that ferrocene based compounds with CNTs modified electrodes have shown excellent ferrocene peaks [49,50,51]. It has been reported that the electrical properties of the composites depend on the aspect ratio, alignment, and even alignment thickness, and dispersion of conductive fillers, and the alignment of MWCNTs in a certain way, viz.…”
Section: Resultsmentioning
confidence: 71%
“…Clearly, the data indicate that the incorporation of ZnO NPs seems to be able to slightly improve the sensitivity. However, the modified electrodes based on only any single material, even the simple combination of two components including MWCNTs, PMAEFc, and ZnO NPs surprisingly do not show well-defined redox peak currents, which is different from the results reported by quite a lot of references in that ferrocene based compounds with CNTs modified electrodes have shown excellent ferrocene peaks [49,50,51]. It has been reported that the electrical properties of the composites depend on the aspect ratio, alignment, and even alignment thickness, and dispersion of conductive fillers, and the alignment of MWCNTs in a certain way, viz.…”
Section: Resultsmentioning
confidence: 71%
“…The morphological dissimilarity of the anode and cathode eludes to the importance of capacity matching of our PVFc-CNT/PPy-DBS asymmetrics ystem.I nf act, optimal capacity matching of the electrodes plays ac entral role in the performance of asymmetric electrochemically-modulated systems, as it improves the overall cell efficiency and capacity utilization by avoiding surfacep arasitic reactions. [42,43] To this end, we conducted as eries of cyclic voltammetry experiments with the three-electrode configuration on asymmetric cells with various PPy loadings (and af ixed PVFc loading) and calculated the capacity of the individual electrodes (Figure 4). The aim here is to determine the optimum ratio between the PVFc and PPy loadings.…”
Section: Resultsmentioning
confidence: 99%
“…Three complicating features of this system to consider regarding separations are (1) the high overall electrolyte concentrations, (2) the need to keep the main stream of electrolyte (i.e., what remains after separating out the decayed species) almost entirely uncontaminated from the separations process and the further desire to recover the decayed species intact as well for reuse in the system, and (3) the likely similar characteristics of the decayed species being targeted for separations and the active species that must remain in the electrolyte. Methods for separating organics via exploitation of differences in the physical, chemical, and/or electrochemical properties exist and can even separate similar compounds (e.g., isomers) [74,75]. It seems reasonable to assume that expertise in separating decay product lies within the process industry given the requirements to create products of sufficient purity.…”
Section: Remediating Capacity Loss For Asymmetric Chemistries With Active Species Of Finite Lifetime: Active-species Replacementmentioning
confidence: 99%